2020
DOI: 10.1097/sla.0000000000004356
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Noninvasive Imaging for Assessment of Axillary Response After Neoadjuvant Systemic Therapy in Clinically Node-positive Breast Cancer

Abstract: Objective: The purpose of this study was to perform a systematic review and meta-analysis to determine the diagnostic performance of current noninvasive imaging modalities for assessment of axillary response after neoadjuvant systemic therapy (NST) in clinically node-positive breast cancer patients. Summary of Background Data: NST can lead to downstaging of axillary lymph node disease. Imaging can potentially provide information about the axillary respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 37 publications
2
29
2
1
Order By: Relevance
“…The use of non-invasive imaging after NACT cannot replace axillary surgery. In a meta-analysis looking at how reliable imaging is in determining nodal pathological complete response (pCR), the outcome of 2380 patients in 13 studies with non-invasive imaging after NACT was compared with axillary surgery [ 19 ]. The study showed an axillary pCR of 39.5% (941/2380).…”
Section: Clinically Node-positive Breast Cancermentioning
confidence: 99%
“…The use of non-invasive imaging after NACT cannot replace axillary surgery. In a meta-analysis looking at how reliable imaging is in determining nodal pathological complete response (pCR), the outcome of 2380 patients in 13 studies with non-invasive imaging after NACT was compared with axillary surgery [ 19 ]. The study showed an axillary pCR of 39.5% (941/2380).…”
Section: Clinically Node-positive Breast Cancermentioning
confidence: 99%
“…The diagnostic performance of current non-invasive imaging modalities to assess ALN status, including magnetic resonance imaging (MRI) and axillary ultrasound, are limited by their high false-negative rates [7]. Nowadays, the development of radiomics in the aspects of tumor diagnosis, treatment decisions, and prognosis prediction is encouraging, and breast cancer is one of the focal areas in the exploration [8À10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the diagnostic performance of non-invasive imaging, including PET and magnetic resonance imaging (MRI), for assessment of axillary response after NST in clinically node-positive breast cancer was the focus of a recent systematic review and meta-analysis. The authors concluded that the diagnostic performance of current noninvasive imaging modalities was too limited to accurately assess axillary response after NST in clinically node-positive breast cancer patients (13).…”
Section: Predictors Of Pcrmentioning
confidence: 99%